UJI TOKSISITAS SUBKRONIS EKSTRAK CURCUMA BEBAS MINYAK ATSIRI (ECBA) DITINJAU DARI PARAMETER PROFIL LEUKOSIT PADA TIKUS PUTIH GALUR WISTAR - Farida, Verda; Ikawati, Zullies; Pramono, Suwidjiyo (Universitas Ahmad Dahlan, 2014)
The effect of Volatil Oil of Curcuma Extraxt or Curcumin extract withcentration of essential oil in reducing the levels of cholesterol in the blood has beenECBA as antihyperlipidemic agent is given for a long - term therapeutic purpose. Thisexperiment was performed to investigate the subchronic toxicity of ECBA on leukocytes profile ofWistar rats. ECBA was investigated at dose 15 mg, 120 mg, and 960 mg/200 g body weight for 90days in 40 male Wistar rats. CMC-Na was used for control. The blood was examined for theleukocytes profile on day 0, 45, and 90. The rats were still maintained under experimental conditionswithout giving ECBA until day 105 for the reversibility test. The result showed that the administrationof ECBA for 90 days did not affect leukocytes profile of Wistar rats.